Synthesis and antimicrobial activity of chiral quaternary N-spiro ammonium bromides with 3',4'-dihydro-1'H-spiro[isoindoline-2,2'-isoquinoline] skeleton - Bielawski K; Leszczyńska K; Kałuża Z; Bielawska A; Michalak O; Daniluk T; Staszewska-Krajewska O; Czajkowska A; Pawłowska N; Gornowicz A (Drug Design, Development and Therapy, 2017)
Krzysztof Bielawski,1 Katarzyna Leszczyńska,2 Zbigniew Kałuża,3 Anna Bielawska,4 Olga Michalak,3 Tamara Daniluk,2 Olga Staszewska-Krajewska,3 Anna Czajkowska,4 Natalia Pawłowska,1 Agnieszka Gornowicz4 1Department of Synthesis and Technology of Drugs, 2Department of Microbiology, Medical University of Bialystok, Bialystok, 3Institute of Organic Chemistry, Polish Academy of Sciences, Warsaw, 4Department of Biotechnology, Medical University of Bialystok, Bialystok, Poland Abstract: A new class of highly functionalized tetrahydroisoquinolines with a quaternary carbon stereocenter was synthesized starting from an easily accessible l-tartaric acid. Nine strains of bacteria (Staphylococcus aureus, Streptococcus pyogenes, Streptococcus mutans, Streptococcus salivarius, Bacillus subtilis, Enterococcus faecalis, Moraxella catarrhalis, Escherichia coli, Campylobacter jejuni) were used for the determination of minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of synthesized compounds. The influence of analyzed compounds on viability and induction of apoptosis in human skin fibroblasts was determined. A majority of the synthesized compounds showed the strongest antibacterial properties toward some gram-negative bacteria (M. catarrhalis and C. jejuni) with a high level of selectivity. High antibacterial compounds have bactericidal activity ratio MBC/MIC =4. Our studies also proved that the novel compounds do not possess cytotoxic and proapoptotic potential in normal cells. Keywords: quaternary ammonium compounds, tetrahydroisoquinolines, antimicrobial activity, antibiotic resistance